Embryonic miRNA Profiles of Normal and Ectopic Pregnancies - Dominguez, Francisco (Public Library of Science, 2014)
Our objective was to investigate the miRNA profile of embryonic tissues in ectopic pregnancies (EPs) and controlled abortions (voluntary termination of pregnancy; VTOP). Twenty-three patients suffering from tubal EP and twenty-nine patients with a normal ongoing pregnancy scheduled for a VTOP were recruited. Embryonic tissue samples were analyzed by miRNA microarray and further validated by real time PCR. Microarray studies showed that four miRNAs were differentially downregulated (hsa-mir-196b, hsa-mir-30a, hsa-mir-873, and hsa-mir-337-3p) and three upregulated (hsa-mir-1288, hsa-mir-451, and hsa-mir-223) in EP compared to control tissue samples. Hsa-miR-196, hsa-miR-223, and hsa-miR-451 were further validated by real time PCR in a wider population of EP and control samples. We also performed a computational analysis to identify the gene targets and pathways which might be modulated by these three differentially expressed miRNAs. The most significant pathways found were the mucin type O-glycan biosynthesis and the ECM-receptor-interaction pathways. We also checked that the dysregulation of these three miRNAs was able to alter the expression of the gene targets in the embryonic tissues included in these pathways such as GALNT13 and ITGA2 genes. In conclusion, analysis of miRNAs in ectopic and eutopic embryonic tissues shows different expression patterns that could modify pathways which are critical for correct implantation, providing new insights into the understanding of ectopic implantation in humans.